2021
DOI: 10.1186/s12864-021-07411-w
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of codon and amino acid use for translational functions in highly expressed cricket genes

Abstract: Background For multicellular organisms, much remains unknown about the dynamics of synonymous codon and amino acid use in highly expressed genes, including whether their use varies with expression in different tissue types and sexes. Moreover, specific codons and amino acids may have translational functions in highly transcribed genes, that largely depend on their relationships to tRNA gene copies in the genome. However, these relationships and putative functions are poorly understood, particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Studies on CpG depletion, considered a reliable indicator of DNA methylation, have revealed that DNA methylated genes tend to perform housekeeping functions across insects including holometabolous and hemimetabolous ones (Ylla et al 2021). In addition to the epigenomics described above, the genome and transcriptome in crickets have been used for studying the sex-biased gene expression regulation, which is linked to protein sequence evolution (Whittle et al 2021a) and the relationship between codon usage frequency and expression level in different tissues and sexes (Whittle et al 2021b).…”
Section: Othersmentioning
confidence: 99%
“…Studies on CpG depletion, considered a reliable indicator of DNA methylation, have revealed that DNA methylated genes tend to perform housekeeping functions across insects including holometabolous and hemimetabolous ones (Ylla et al 2021). In addition to the epigenomics described above, the genome and transcriptome in crickets have been used for studying the sex-biased gene expression regulation, which is linked to protein sequence evolution (Whittle et al 2021a) and the relationship between codon usage frequency and expression level in different tissues and sexes (Whittle et al 2021b).…”
Section: Othersmentioning
confidence: 99%
“…These were osk , Tdrd5 , Tdrd7 , limkain b1 , and an uncharacterized gene with annotation ID GBI_15344 (Supplementary File 2). In transcriptomes previously generated from the adult brain (55), we detected levels of all four non- oskar genes at levels at least as high as that detected for osk (Suppl. Figure S4, Suppl.…”
Section: Discussionmentioning
confidence: 64%
“…This search retrieved five genes (GBI_01840 “ oskar ”, GBI_13502 “ TDRD5/tejas ”, GBI_15344 “ uncharacterized ”, GBI_15604 “ limkain b1 ”, GBI_03370 “ TDRD7/tapas ”). We assessed expression of these genes in brains and gonads using previously published RNA-seq libraries (55) available at NCBI (PRJNA564136). We analyzed the RNA-seq data as in (16), including removing adapters and reads shorter than 20 nucleotides with Cutadapt v3.4 (65) and quantifying the gene expression in transcripts per million (TPM) with RSEM v1.2.29 (66), using STAR v2.7.0e1 (67) as read mapper against the G. bimaculatus genome (36) (Suppl.…”
Section: Methodsmentioning
confidence: 99%
“…The FPKM of the S1|c21076_g1 and the S2|c17052_g1 sequences indicated low and high expression levels, respectively. Genes using the codons that are recognized by more abundant tRNA molecules may be translated more efficiently and with fewer mistakes than genes that use less frequent codons [ 54 , 55 ]. Nelson et al found that the high frequency of AGA/AGG codons present in the HCcAg and HU IFNa2 genes could be one of the factors limiting its expression in Escherichia coli [ 47 ].…”
Section: Discussionmentioning
confidence: 99%